An Examination of the Efficiency, Foreclosure, and Collusion Rationales for Vertical Takeovers - Shenoy, Jaideep (Management Science, 2012)
We investigate the efficiency, foreclosure, and collusion rationales for vertical integration in a large sample of vertically related takeovers. The efficiency rationale, as discussed under the transaction cost economics and property rights theories, posits that vertical integration mitigates contractual inefficiencies between suppliers and customers (termed as holdup) and provides incentives to undertake relationship-specific investments. In contrast, the foreclosure and collusion rationales suggest that vertical integration is anticompetitive in nature. Specifically, the foreclosure argument suggests that vertical integration is used to raise costs of rival firms, and the collusion argument suggests that vertical integration facilitates coordination between the integrated firm and its rivals. To distinguish between the three hypotheses, we examine (1) the announcement period wealth effects to the merging firms, rival firms, and customer firms; and (2) the operating performance changes to the merging firms in vertical takeovers. We find that firms expand their vertical boundaries consistent with an efficiency enhancing rationale. This paper was accepted by Brad Barber, finance.